Histopathological Features of Parathyroid Adenoma and 18F-Choline Uptake in PET/MR of Primary Hyperparathyroidism. (February 2022) - Liberini, Virginia; Morand, Gregoire B.; Rupp, Niels J.; Orita, Erika; Deandreis, Désirée; Broglie Däppen, Martina; Hofbauer, Marlena; Maurer, Alexander; Husmann, Lars; Mader, Cäcilia E.; Grünig, Hannes; Alharbi, Abdullah A.; et al.
Abstract : Supplemental digital content is available in the text. Abstract : Background: The aim of this study was to assess the relationship between the histopathological properties of hyperfunctioning parathyroids and parathyroid 18 F-choline uptake. Patients and Methods: A total of 31 parathyroid adenomas were retrospectively analyzed in patients with primary hyperparathyroidism and preoperative 18 F-choline PET/MR. PET/MR parameters of parathyroid glands (SUVmax and target-to-background ratio in early-phase [EP] and late-phase [LP]), MRI volume, preoperative parathyroid hormone (PTH) serum concentration, and postoperative histopathology (predominant cell type and growth pattern of adenoma cells, location and size of adenoma) were assessed. The relationship of PET/MR parameters, PTH, and histological parameters was determined using linear regression, Spearman correlation and Kruskal-Wallis test. Results: The median volume of parathyroid adenoma was 421.78 ± 142.46 mm 3 (46.39–4412.69). Adenomas were predominantly composed of chief, water-clear, and oncocytic/oxyphilic cells in 27/31, 2/31, and 2/31 cases, respectively. The growth pattern was predominantly solid, follicular, and trabecular in 18/31, 8/31, and 5/31, respectively. The SUVmax was 6.71 ± 3.39 in EP and 6.91 ± 3.97 in LP. Follicular growth pattern had slightly higher EP SUVmax (trabecular: 4.12 ± 0.56; solid: 6.62 ± 3.19; follicular: 8.56 ± 3.96; P = 0.046). Spearman correlation showed strong positive correlation between volume and both EP and LP SUVmax (0.626; P = 0.0001 and 0.576; P = 0.0001, respectively). Linear regression analysis revealed significant correlation between PTH level and EP and LP SUVmax (both P = 0.001); in contrast, no correlation was found between PTH level and both cell type and growth pattern. Conclusions: Our findings suggest that 18 F-choline uptake of parathyroid adenomas might be associated both with the histological growth pattern and adenoma volume, but not with a specific cell type.